Análisis del perfil de textura del Queso Mantecoso comercial - Villalobos Araujo, Ana Paula (2017)
The aim of the present work was to determine the texture profile of commercial Mantecoso cheese, four brands were chosen: CEFOP, El Andino, Huacariz and Chugur. The Texture Profile Analysis of the processed cheeses was determined using a TA.HDPlus Texture Analyzer with a 5 kg force load cell. The test was performed by a 50% double compression cycle using a 75 mm compression platen, a crosshead speed of 1 mm/s and a trigger force of 4 g. The samples were cut into cubes and stored at temperature of 21 °C. The textural parameters included hardness, adhesiveness, springiness, cohesiveness and gumminess. In addition, analyzes of moisture and acidity were performed. The results showed that the values of hardness and cohesiveness were significantly different in all analyzed brands (p <0.05). In vacuum-packed cheeses, the parameter that did not show significant difference was the springiness; whereas in the cheeses packaged at atmospheric pressure, the similar parameter was the adhesiveness. Mantecoso cheese showed less hardness, springiness and cohesiveness than other commercial ripened cheeses such as Cheddar, Gouda and Emmental. However, it also showed higher hardness and adhesiveness than the spreadable cheeses and Camembert cheese.